North American pitseed goosefoot (Chenopodium berlandieri) is a genetic resource to improve Andean quinoa (C. quinoa) - Maughan, Peter J. (2024)
Pitseed goosefoot (Chenopodium berlandieri) is a free-living North American member of an allotetraploid complex that includes the Andean pseudocereal quinoa (C. quinoa). Like quinoa, pitseed goosefoot was domesticated, possibly independently, in eastern North America (subsp. jonesianum) and Mesoamerica (subsp. nuttaliae). To test the utility of C. berlandieri as a resource for quinoa breeding, we produced the whole-genome DNA sequence of PI 433,231, a huauzontle from Puebla, México. The 1.295 Gb genome was assembled into 18 pseudomolecules and annotated using RNAseq data from multiple tissues. Alignment with the v.2.0 genome of Chilean-origin C. quinoa cv. ‘QQ74’ revealed several inversions and a 4A-6B reciprocal translocation. Despite these rearrangements, some quinoa x pitseed goosefoot crosses produce highly fertile hybrids with faithful recombination, as evidenced by a high-density SNP linkage map constructed from a Bolivian quinoa ‘Real-1’ × BYU 937 (Texas coastal pitseed goosefoot) F2 population. Recombination in that cross was comparable to a ‘Real-1’ × BYU 1101 (Argentine C. hircinum) F2 population. Furthermore, SNP-based phylogenetic and population structure analyses of 90 accessions supported the hypothesis of multiple independent domestications and descent from a common 4 × ancestor, with a likely North American Center of Origin.